A systemic analysis of the impacts of Product 4.0 on the triple bottom-line of Sustainability. Issue 10 (2022) - Popolo, Valentina; Vespoli, Silvestro; Gallo, Mosè; Grassi, Andrea
Abstract: The advent of innovative technologies is reshaping every aspect of our lives. Smart products incorporating these new technologies have become commonplace in both our private and professional lives. The use of advanced technologies has shown great potential in improving and streamlining various daily activities, but the products that support their deployment in real life present serious threats to the environment. Indeed, the speed at which new technological products are brought onto the market and old ones are discarded is generating a dual negative effect: an exponential increase in electrical and electronic waste and unsustainable exploitation of non-renewable natural resources. This situation in turn can have significant effects on the economic sustainability of our societies, due to the increasing costs of waste disposal and the increasingly limited availability of raw materials. As is evident, the introduction of smart products has its positive and negative sides that influence all aspects of sustainability within a complex structure of cause-effect relationships. Therefore, this article investigates the main variables at play and their interconnections when considering smart products. To analyse the effects of these variables, a Causal Loop Diagram (CLD) is developed and thoroughly discussed. The proposed CLD highlights the sustainability aspects of smart products. In addition, it highlights how the introduction of the so-called "Product 4.0" can be a solution to improve the triple bottom-line of sustainability.